Seismic- and core-based glacial sequence stratigraphy in an overdeepened trough in the northern Alpine foreland of Switzerland - Sebastian Schaller; Bennet Schuster; Sarah Beraus; Marius W. Buechi; Hermann Buness; Flavio S. Anselmetti (Swiss Journal of Geosciences)
Abstract In the context of a project of the International Continental Scientific Drilling Program (ICDP) (DOVE; Drilling Overdeepened Alpine Valleys), a series of boreholes were drilled into buried overdeepened glacial troughs in the central and eastern part of the northern Alpine foreland. The sedimentary records of these overdeepenings, reaching back to the Middle Pleistocene, are essential archives for paleoclimate and a key to better understanding past glaciations and landscape evolution. As part of the project, an over 250 m long succession of unconsolidated Quaternary sediments was recovered from the Basadingen Trough (ICDP 5068_2, NE Switzerland), belonging to the NW part of the former Rhine Glacier’s foreland lobe. The drill site is positioned on a high-resolution 2D seismic line, serving as the basis for a sequence and facies analysis. Acoustic wire-line logging data (vertical seismic profile—VSP) directly links the sediment succession with the seismic data, allowing the establishment of a detailed and unifying seismic- and core-based glacial sequence stratigraphy dividing the strata into chronostratigraphically distinct sedimentary units. Based on this stratigraphy, the overdeepened valley fill could be grouped into three overdeepened glacial sequences, reflecting three pulses of glacial advance and retreat. Furthermore, a 3D model of a segment of the Basadingen Trough was created by combining the 2D seismic lines with the local geological information (i.e., geological maps, existing bedrock models, and drill-logs from core and flush drillings), visualizing the shape of the initial bedrock incision, the multiphase trough-infill architecture, and the overlying non-overdeepened cover. A generic model for a glacio-seismic sequence is developed that underlines the benefits of combining complementary geological and geophysical data in these highly complex depositional settings. The close link of these sequences to glacial advance-retreat cycles contributes to the development of a local glaciation model, as shown for the Basadingen Trough. This approach can be applied to other similar settings in formerly glaciated areas.